Improvement Of Traditional Alveoloplasty in Patients with Congenital Cleft Lip and Palate - Shokhrukh Tolibekovich Shokirov; Ikrom Ilkhomovich Mukimov (Genius Journals, 2021)
The urgency of the problem of developing and improving methods for the surgical treatment of secondary deformities of the upper and lower jaws is determined by the increase in the number of patients with facial skeleton deformities after primary operations on the lip and palate. Numerous studies conducted by domestic and foreign scientists indicate that only the study of the long-term results of treatment of patients with jaw deformities can answer many questions, namely: how effective are improved or developed treatments, is a comprehensive approach, suitable for planning and treating patients with jaw deformities, what should be the sequence and timing of rehabilitation treatment.
Keywords: Cleft Lip And Palate; Secondary Deformities Of The Upper Jaw; Alveoloplasty